A economia dos contratos de parcerias público-privadas: um estudo de caso sobre a concessão da Arena Castelão - Carvalho Júnior, Nestor Marques de (2018)
Fortaleza was chosen to be one of the 12 host cities of the 2014 World Cup, with the requirement of investments in infrastructure and reformulation of Plácido Castelo Stadium by the Government of the State of Ceará, in the FIFA Standard, in the implementation of a new sports arena, which considered the feasibility of the project and promoted it through the granting of the project to the private initiative, using the public-private partnership modality (PPPs). Bettignies and Ross (2007) questioned the possibility of where and how the public administration could allocate resources for the provision of public services, under the temporary domination of the private entity, concluding that PPPs should be effective when there is acceptable quality services at the lowest cost to taxpayers / consumers, considering, among other variables, the marginal cost x the average cost of government loans, with some requirements, such as performance evaluation of the concession object and the contractual counterparts of which with the contractor. Based on a qualitative methodology, based on books and electronic documents, in contrast to Bettignies and Ross's conclusions, it can be seen that, in terms of loan proceeds, the concession was based on a precarious foundation (public administration cost the investment and the obligation to split profits), the contract presented flaws that showed negligence, recklessness and lack of skill of the contractual assignments proposed by the enterprise, non-compliance with performance evaluation criteria, and lack of material evidence of the attestations, payments without evaluation of contractual indicators, among other flaws potentially damaging to the treasury. The venture proved to be unacceptable because, although with the provision of quality services, the costs to users and taxpayers when the accounts are presented to those who attend them or who have an obligation to use their environment are questionable.